Perencanaan Arsitektur Enterprise Menggunakan Framework TOGAF - Zukhruf, Afriza Meigi; Widodo, Aris Puji; Sediyono, Eko (Jurnal Inovtek Polbeng Seri Informatika, 2023)
PKU Muhammadiyah Mayong Hospital is a health institution that focuses on excellent service to patients. The increasing need for service functions is a driving factor for the application of information technology at PKU Muhammadiyah Mayong Hospital. To support the alignment of the application of information systems with the needs of the hospital, a paradigm called enterprise architecture is needed. This study aims to analyze the planning of enterprise architecture using the Open Group Architecture Framework (TOGAF) framework with the Architecture Development Method (ADM) method at PKU Muhammadiyah Mayong Hospital. TOGAF is a generic architectural framework designed to be used in various types and sizes of organizations. ADM is a method that contains a set of activities used in modeling the development of enterprise architecture. This research is expected to be useful for PKU Muhammadiyah Mayong Hospital to integrate business processes with information technology. At each stage of ADM what is done is the process of identifying problems, analyzing problems and solutions to these problems. In this study the stages used only up to the information system architecture. The results of this study are proposed business architecture, data architecture and application architecture.